(untitled) (Comprehensive Journal of Science, 2025)
This study aims to uncover the secrets of the divine order governing the distribution and repetition of the letter Mīm (م) in the opening verses (Fawātiḥ al-Suwar) of the Qur’an (Alif Lām Mīm, Ṭā Sīn Mīm, Ḥā Mīm). It serves as a model demonstrating the integration of numerical inimitability (I‘jāz ‘Adadī) with rhetorical inimitability (I‘jāz Bayānī). The research employed the descriptive-analytical and comparative statistical methodologies to document the precise numerical proportionality of the letter’s recurrence across three distinct groups of Surahs. The study concludes that the frequency of the letter Mīm is not random; rather, it adheres to a precise and intentional order. Furthermore, the analysis established that the numerical density of the Mīm aligns with its semantic weight in the central terms of the Surahs (such as Ummah - Nation, Mawt - Death, Mūsá - Moses) and its phonetic properties (nasal sound/resonance). This integration serves the Qur’anic rhythm and rhetoric, providing empirical evidence that the Qur’anic structure is a holistic miracle in both its quantity and quality. The research recommends integrating the findings of documented numerical inimitability into Islamic Studies to affirm the divine source of the text.